Respostas
respondido por:
21
Calculamos a razão
r = a2 - a1
r = 6 - 1
r = 5
=====
an = a1 + ( n -1 ) * r
a7 = 1 + ( 7 -1 ) * 5
a7 = 1 + 6 * 5
a7 = 1 + 30
a7 = 31
7º termo a7 = 31
r = a2 - a1
r = 6 - 1
r = 5
=====
an = a1 + ( n -1 ) * r
a7 = 1 + ( 7 -1 ) * 5
a7 = 1 + 6 * 5
a7 = 1 + 30
a7 = 31
7º termo a7 = 31
lariissa947:
Obrigada :)
respondido por:
15
P.A. = ( 1, 6, 11, ...) ⇒ r = 5
a₇ = a₁ + ( n-1). r
a₇ = 1 + 6 .5
a₇ = 1 + 30
a₇ = 31
Espero ter ajudado, bons estudos. Abraços
a₇ = a₁ + ( n-1). r
a₇ = 1 + 6 .5
a₇ = 1 + 30
a₇ = 31
Espero ter ajudado, bons estudos. Abraços
Perguntas similares
7 anos atrás
7 anos atrás
7 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás
10 anos atrás